Molecular typing reveals the co-existence of two transmission cycles of American cutaneous leishmaniasis in the Andean Region of Venezuela with Lutzomyia migonei as the vector - Annhymariet Torrellas; Elizabeth Ferrer; Israel Cruz; Héctor de Lima; Olinda Delgado; José Carrero Rangel; José Arturo Bravo; Carmen Chicharro; Ivonne Pamela Llanes-Acevedo; Michael A Miles; María Dora Feliciangeli (Memorias do Instituto Oswaldo Cruz, 2018)
BACKGROUND The transmission routes for American cutaneous leishmaniasis (ACL) are in flux, so studies examining its transmission in humans, mammalian hosts, and sand fly vectors are urgently needed. OBJECTIVES The aim of this work was understand the epidemiological cycles of Leishmania spp., which causes ACL in the Andean Region of Venezuela, by identifying the Leishmania and the sand fly species involved in human and dog infections. METHODS Thirty-one biopsies from patients in Mérida and Táchira states with suspected ACL were studied by both parasitological tests (cultures and hamster inoculation) and a molecular test [Internal transcribed spacer 1 (ITS1) nested polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP)]. We also conducted a survey to detect Leishmania infection in dogs (Immunifluorescence antibody test and ITS1 nested PCR-RFLP) and sand flies (ITS1 nested PCR-RFLP) from El Carrizal, a highly endemic focus of ACL in Venezuela. FINDINGS Three different Leishmania species were identified in the clinical samples from humans (Leishmania braziliensis, L. guyanensis, and L. mexicana) and dogs (L. guyanensis and L. mexicana). The predominant sand fly species found were those from the Verrucarum group (infected with L. mexicana) and Lutzomyia migonei (infected with L. guyanensis and L. mexicana). MAIN CONCLUSIONS We show that Lu. migonei may be the putative vector in two ACL epidemiological cycles, involving L. guyanensis and L. mexicana. We also report for the first time the presence of L. guyanensis in domestic animals.